PENGARUH KONDISI EKONOMI TERHADAP PENGGUNAAN SHOPEEPAY MELALUI PERILAKU KONSUMTIF SEBAGAI VARIABEL INTERVENING - Dewi Kusuma Wardani; Yuan Novita Indriyanti (Bajang Institute, 2022)
This study aims to determine the effect to economic conditions on the use of shopeepay through consumptive behavior as an intervening variable. This study uses descriptive quantitative and primary data using a questionmore. The number of samples in this study was 140 respindents of Muslim students studying in Yogyakarta. Sampling in this study using snowball sampling. This study gives results economic conditions have a negative efeect on the use of shopeepay, economic conditions do not affect consumptive behavior, consumptive behavior does not affect the use of shopeepay, economic conditions do not affect the use of shopeepay through consumptive behavior.